2012
DOI: 10.1111/j.1365-2435.2012.01968.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlated behaviour and stress physiology in fish exposed to different levels of predation pressure

Abstract: Summary1. Natural selection can generate correlated suites of phenotypic traits by acting independently on physiological and behavioural characters or on mechanisms that exert pleiotropic actions. 2. Current theory, supported by artificial selection studies, suggests that physiological and behavioural stress responses are at least partially under genetic control and covary in a predictable manner. Indeed, physiological mechanisms such as hormonal stress responsiveness may underlie variation in behaviour, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
97
3
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(108 citation statements)
references
References 47 publications
7
97
3
1
Order By: Relevance
“…However, under laboratory circumstances, animals lack many of the behavioural options to respond to predators, and given that the perception of control is a prime determinant of the stress response [2], the relevance of these studies to naturally occurring glucocorticoid secretion is not clear. Indeed, in the few cases in which fish from field populations were examined, those living among abundant predators had lower cortisol production and reduced stress responses compared with fish in low-predation environments [20,44]. We found that basal and stress-induced cortisol levels were unrelated to predator exposure and tail injury, indicating that B. occidentalis regulate their glucocorticoid levels independently of predator stimuli.…”
Section: Discussion (A) Predation Pressure Correlates Negatively Withmentioning
confidence: 79%
See 1 more Smart Citation
“…However, under laboratory circumstances, animals lack many of the behavioural options to respond to predators, and given that the perception of control is a prime determinant of the stress response [2], the relevance of these studies to naturally occurring glucocorticoid secretion is not clear. Indeed, in the few cases in which fish from field populations were examined, those living among abundant predators had lower cortisol production and reduced stress responses compared with fish in low-predation environments [20,44]. We found that basal and stress-induced cortisol levels were unrelated to predator exposure and tail injury, indicating that B. occidentalis regulate their glucocorticoid levels independently of predator stimuli.…”
Section: Discussion (A) Predation Pressure Correlates Negatively Withmentioning
confidence: 79%
“…In the presence of abundant predators, prey probably move more cautiously and in a more limited range [13,23,43] (however, see [44]). Thus, predators could influence prey by directly influencing the brain through the 'physiology of fear' (e.g.…”
Section: Discussion (A) Predation Pressure Correlates Negatively Withmentioning
confidence: 99%
“…Consequently, stress may reduce reproductive success (Schreck et al 2001) and disrupt trophic interactions (Archard et al 2012), from which it follows that stress may not only negatively affect individuals but also contribute to population decline and the possible extinction of species (Schaaf et al 2008). Nevertheless, natural populations typically consist of individuals of a range of different copying styles and such a mixture means that individuals will vary in how well they fare under stressful situations but also provides a population with some flexibility to persist (Koolhaas et al 1999, Korte et al 2005.…”
Section: Discussionmentioning
confidence: 99%
“…Risk taking was assayed using an emergence from shelter/openfield exploration paradigm (e.g. Archard et al, 2012). Individuals were acclimated for 2 h beginning at 10:00 h in an enclosure constructed from opaque black corrugated plastic.…”
Section: Behavioral Assaysmentioning
confidence: 99%